2009
DOI: 10.1590/s0102-311x2009000400009
|View full text |Cite
|
Sign up to set email alerts
|

Incidência de cárie dentária em adolescentes em município do Nordeste brasileiro, 2006

Abstract: O presente estudo teve como objetivo analisar a incidência da cárie dentária em adolescentes associada à condição sócio-econômica, acesso a serviços e autopercepção. É um estudo longitudinal por meio de levantamento epidemiológico de cárie e questionário estruturado com amostra composta por 688 adolescentes residentes no Município de Sobral, Ceará, Brasil. A incidência aumentou progressivamente com a idade, passando de 1,60 nos adolescentes com 12 anos até 2,28 para os com 15 anos, registrando-se uma incidênci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
7
0
10
Order By: Relevance
“…The consumption of cariogenic products, especially where intake is frequent, seems to be the most widely accepted behavioral factor in the development of the caries process 39 . This study showed that the consumption of processed products may be responsible for the experience of caries in adolescents in the city, particularly when the frequency of consumption of these items is taken into account, as individuals who ingest these foods may have a greater prevalence of caries than those who do not and the increase in weekly consumption contributed towards the increase in the number of adolescents with carious lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of cariogenic products, especially where intake is frequent, seems to be the most widely accepted behavioral factor in the development of the caries process 39 . This study showed that the consumption of processed products may be responsible for the experience of caries in adolescents in the city, particularly when the frequency of consumption of these items is taken into account, as individuals who ingest these foods may have a greater prevalence of caries than those who do not and the increase in weekly consumption contributed towards the increase in the number of adolescents with carious lesions.…”
Section: Discussionmentioning
confidence: 99%
“…O nível educacional da mãe tem sido considerado um preditor de cárie, assim como influencia os hábitos de higiene bucal dos filhos 20,21,22 . Contudo, na análise univariada realizada no presente estudo, diferenças no consumo de dentifrício entre os estratos de nível educacional não foram encontradas.…”
Section: Discussionunclassified
“…Mesmo assim, o percentual de domicílios com renda de até 2 SM foi semelhante ao reportado pelo IBGE no último censo realizado na região (Censo Demográfico 2000. http://www.ibge.gov.br). Além disso, o tamanho da amostra do presente estudo é semelhante a diversos estudos que abordam hábitos de higiene bucal de cidades de porte maior 9,26 e de cidades de porte semelhante ao de Passo Fundo 22,25 .…”
Section: Discussionunclassified
“…Studies have stressed that through small investments in preventive actions it is possible to save many curative actions due to a reduction in the prevalence of caries and the great amplitude provided by this method (NUNES et al, 2004). Preventive actions activities, such as, education and motivation are directed to people concerning their oral hygiene habits (DITTERICH et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Preventive actions activities, such as, education and motivation are directed to people concerning their oral hygiene habits (DITTERICH et al, 2007). Also included as prevention methods, are water fluoridation of public water supply (MARINHO et al, 2006;PEREIRA, 2003;NUNES et al, 2004)), as well as salt (WARPEHA et al, 2001), and the use of fluoridated dentifrice (PEREIRA, 2003).…”
Section: Discussionmentioning
confidence: 99%